The Analysis of The Factors Influencing The Development of Foreign Economic Activity in The National Companies and The Management of Export-Oriented Production: Analisis Faktor-Faktor Yang Mempengaruhi Perkembangan Kegiatan Ekonomi Asing Perusahaan Nasional dan Pengelolaan Produksi Berorientasi Ekspor - Akhmedov , I. A (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2018)
This paper investigates major points of the experience of The analysis of the factors influencing the development of foreign economic activity in the national companies and the management of export-oriented production. On this way, management of export-oriented production and reliable terms were analyzed both theoretically and practically. Moreover, investigations of the well developed countries were learned, factors influencing the development of foreign economic activity in the national companies in comparison with local establishment and implementations. Final conclusions were done in order to reach better deployment in these areas.